2008
DOI: 10.1007/s10522-008-9200-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 40% restriction of dietary amino acids (except methionine) on mitochondrial oxidative stress and biogenesis, AIF and SIRT1 in rat liver

Abstract: Previous studies have shown that the decrease in mitochondrial reactive oxygen species (mitROS) generation and oxidative damage to mitochondrial DNA (mtDNA) that occurs during life extending dietary restriction also occurs during protein or methionine restriction, whereas it does not take place during carbohydrate or lipid restriction. In order to study the possible effects of other amino acids, in this investigation all the dietary amino acids, except methionine, were restricted by 40% in male Wistar rats (RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…83 In addition, we have recently found that 40% MetR also decreases mtROSp, %FRL, and 8-oxodG in mtDNA and reverses aging-related increases in protein modification when implemented at old age (during 7 weeks in 24-month-old rats). 82 All those results, taken together, indicate that the lowered ingestion of methionine during MetR (and PR and DR) is responsible for the decreases in mitochondrial ROSp and oxidative stress observed in MetR (and PR and DR), and possibly for all (during PR and MetR) or part (during DR) of the life-extension effect observed during these dietary manipulations.…”
Section: Role Of Mtros Generation and Oxidative Damagementioning
confidence: 93%
“…83 In addition, we have recently found that 40% MetR also decreases mtROSp, %FRL, and 8-oxodG in mtDNA and reverses aging-related increases in protein modification when implemented at old age (during 7 weeks in 24-month-old rats). 82 All those results, taken together, indicate that the lowered ingestion of methionine during MetR (and PR and DR) is responsible for the decreases in mitochondrial ROSp and oxidative stress observed in MetR (and PR and DR), and possibly for all (during PR and MetR) or part (during DR) of the life-extension effect observed during these dietary manipulations.…”
Section: Role Of Mtros Generation and Oxidative Damagementioning
confidence: 93%
“…Studies have shown that methionine restriction can decrease mitochondrial ROS production and oxidative stress (Caro et al 2009a). Restriction of dietary amino acids other than methionine decreases mitochondrial protein oxidation and increases SIRT1 in rat liver (Caro et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…While feeding with PREMD significantly decreased protein carbonyl levels both in the liver homogenate and mitochondria of aging rats, it significantly prevented 8-OHdG formation only in mtDNA. There is limited number of studies evaluating the effects of PREMD on aging (Caro et al, 2009a(Caro et al, , 2009b. In these studies, 7 weeks old Wistar rats fed with PREMD for seven weeks did not exhibit any beneficial effects neither on superoxide and peroxide production rates nor 8-OHdG formation in the liver mitochondria.…”
Section: Discussionmentioning
confidence: 98%